PENGARUH KOMPETENSI PEDAGOGIK GURU KIMIA TERHADAP MOTIVASI DAN PRESTASI BELAJAR SISWA KELAS XI IPA SMA DI KELURAHAN SENTANI KOTA - TIRO, ABDUL RACHMAN; SIREGAR, TIURLINA (Jurnal Ilmu Pendidikan Indonesia, 2018)
This Research is suppose to : (1) To know the relationship between Competence Pedagogic Teacher Chemistry against Motivation Student Class XI Science from high school in the Village of Sentani City, (2) determine the relationship between Competence Pedagogic Teacher Chemistry against Student Results Class XI Science from high school in the Village of Sentani City (3) determine the effect of Competence Pedagogic Teacher Chemistry against Motivation Student Class XI Science from high school in the Village of Sentani City. (4) Effect of Competence Pedagogic Teacher Chemistry against Student Results Class XI Science from high school in the Village of Sentani City. The results showed that: (1) there is a weak relationship between Competence Pedagogic Teacher Chemistry against Motivation Student Class XI Science from high school in the Village of Sentani City. This is indicated by the correlation coefficient of 0,386 with a coefficient determinant of 14,9 %. (2) there is a weak relationship between competence Pedagogic Teacher Chemistry against Student Results Class XI Science from high school in the Village of Sentani City. This is indicated by the correlation coefficient of 0,231 with a coefficient determinant of 5,4 % (3) Based on the hypothesis testing results obtained with the t test value of t (5,165) > t table (1,701) which states that in the study of Ho rejected and Ha is accepted, there is effect of Competence Pedagogic Teacher Chemistry against Motivation Student Class XI Science from high school in the Village of Sentani City (4) Based on the hypothesis test results obtained with the t test value of t (5,165) > t table (1,701) which states that in the study of Ho rejected and Ha accepted, means that there is a significant effect of Competence Pedagogic Teacher Chemistry against Student Results Class XI Science from high school in the Village of Sentani City. In other words, pedagogical competence chemistry teacher affects motivation and learning chemistry, but its influence is weak. Keywords: Pedagogic Competence, Motivation to Learn, Student Learning Outcomes, Chemistry